Gender Representation in Men’s and Women’s Fashion Magazine - Marselus Suarta Kasmiran; Ouda Teda Ena (Yayasan Visi Intan Permata, 2019)
This research aims to study the use of basic and specific color terms used in men’s and women’s magazines. The use of specific color terms was proposed by Lakoff (1973). The specific and basic color terms may distinguish the gender of the writers in the magazines. The study analyzed women’s writings in Cosmopolitan Magazine published electronically by https://www.cosmopolitan.com/ and men’s writings in GQ Magazine published electronically by https://www.gq.com/. The data was analyzed using Lakoff’s (1975) and Steinvall’s (2002) theoretical frameworks. Lakoff (1973) argued that women used language features differently. One of the language features stated by Lakoff (1973) was the use of specific color terms. The findings of the research show that there has been a change of specific color term usages, both genders are now using basic and specific color terms. However, men use less specific color terms. The use of language features may be affected by values – ideology, culture and personality from the language users.